2011
DOI: 10.4103/0256-4947.84627
|View full text |Cite
|
Sign up to set email alerts
|

Caudal epidural block in children and infants: retrospective analysis of 2088 cases

Abstract: BACKGROUND AND OBJECTIVES:Regional anesthesia is usually preferred as caudal block via the epidural space. However, the number of large-scale studies including pediatric caudal blocks is small. The objective of this study was to evaluate complications and side effects of local anesthetics and adjuvant drugs.DESIGN AND SETTING:Retrospective, descriptive study of cases occurring during the period December 2007 to October 2009.METHODS:Of 4815 medical records were screened, 2088 pediatric cases were identified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…Previous studies demonstrated that PI could provide an early and reliable indicator of the onset of epidural anesthesia and intravascular injection of epinephrine-containing epidural test dose in adults [5, 7]. However, different from epidural anesthesia or epidural testing dose in conscious adult patients, caudal blocks in pediatric patients were mostly performed under sedation or general anesthesia, such as ketamine or sevoflurane [8, 9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that PI could provide an early and reliable indicator of the onset of epidural anesthesia and intravascular injection of epinephrine-containing epidural test dose in adults [5, 7]. However, different from epidural anesthesia or epidural testing dose in conscious adult patients, caudal blocks in pediatric patients were mostly performed under sedation or general anesthesia, such as ketamine or sevoflurane [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, PI is still able to detect onset of successful caudal block much earlier and more consistently than either MAP or HR. The drawback in our study was that we imposed arbitrary criteria on the endpoint being studied [5], although these endpoints were based on previous published data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dural puncture was reported by Beyaz et al. (1) in 0.19% of patients (4/2088), aged 18 days–11 years. Unfortunately, possible causes for dural punctures were not further investigated.…”
Section: Discussionmentioning
confidence: 93%
“…More specific to caudal blocks, one retrospective analysis of 2088 caudal blocks [8] found the following complications; vessel puncture (1.9%), subcutaneous infiltration (1.5%) and dural puncture (0.2%). Other known complications are infection, haematoma, motor block, urinary retention and bowel perforation.…”
Section: Caudal Analgesiamentioning
confidence: 99%